A multiplex nested PCR assay for the simultaneous detection of genetically modified soybean, maize and rice in highly processed products - Jinxia, Ao; Qingzhang, Li; Xuejun, Gao; Yanbo, Yu; Lu, Li; Minghui, Zhang (Food control, 2011)
The use of genetically modified organisms (GMOs) as food products becomes more and more widespread. The European Union has implemented a set of very strict procedures for the approval to grow, import and/or utilize GMOs as food or food ingredients. Thus, analytical methods for detection of the GMOs are necessary in order to verify compliance with labeling requirements. There are few effective screening methods for highly processed GM (genetically modified) products. Four genes (CP4-EPSPS, Cry1A(b), BAR, and, PAT) are common exogenous genes used in commercialized transgenic soybean, maize, and rice. In the present study, a multiplex nested polymerase chain reaction (PCR) method was developed to simultaneously detect the four exogenous genes and one endogenous gene in two runs. We tested eleven representative highly processed products samples (soya lecithin, soya protein powder, chocolate beverage, infant rice cereal, soybean refine oil, soybean salad oil, maize oil, maize protein powder, maize starch, maize jam) using the developed method, and amplicons of endogenous gene and transgenic fragments were obtained from all the processed products except for soybean refined oil, soybean salad oil and maize oil, and the sensitivity was 0.005%. These results indicate that multiplex nested PCR is appropriate for qualitative detection of transgenic soybean, maize and rice in highly processed products except for refined oil.